Smart platform for the analysis of cupula deformation caused by otoconia presence within SCCs. Issue 2 (25th January 2019) - Vulović, Radun; Nikolić, Milica; Filipović, Nenad
Abstract: In this paper, we first briefly describe the mechanical model of cupula deformation with the appropriate analytical solution. Then, we present the numerical solution of the same problem and compare it with the analytical one. Besides, we provide another numerical solution based on the Finite Element Method procedure, in an effort to encompass a more realistic approach to the problem such as considering the real geometry of the SCCs and the obstruction of the fluid flow during head movement due to the presence of otoconia. As a result, we obtain fifty solutions for a head rotation angle in a range from 0° to 120°, taking into account that such a manoeuvre lasts exactly 3 seconds. In the end, we present a mobile client–server application for visualising the finite element solutions in a way that is convenient for the clinical practice.